An Investigation into the Effect of Conversational Implicature-Based Instruction on Improving EFL Learners’ Illocutionary Competence. The Case of Third year students of English at the University of M’sia - Hadjer ZEGHOUGH, Sarra LAICHE (My University, 2020)
indirectly. | V Abstract From a neo-Gricean perspective, a conversation is whether conventional or non-conventional. EFL students are determined to master the competency of deciphering the non-conventional utterances to sustain a successful rate of a contextual conversation. Accordingly, the present study aims to investigate the effect of conversational implicature-based instruction on improving EFL students’ illocutionary competence. The study targets 35 third year EFL students and five (5) teachers at the English language department at the University of M’sila. The current study is a mixed method oriented research using an exploratory descriptive design to bring about the objectives and answer the questions under investigation. A discourse completion test, a questionnaire and an interview were virtually distributed on the sample to assess students' awareness of implicature’ use , their performance in two small-scale tests of the same construct and to investigate teachers' perceptions and their implicature based instruction in the classroom. The results reveal that teachers occasionally i(nstruct their students using different approaches implicitly in their classes. Henceforth, teachers’ conversational implicature instruction are insufficient and limited which elucidate students’ moderate awareness of conversational implicature comprehension, and good scores with significant differences in the discourse completion test. Consequently, it is suggested to integrate conversational implicature instruction into EFL learning setting for the sake of enhancing students’ illocutionary competence therefore minimizing communication breakdowns and pragmatic failure.
Keywords: Key words: Conversational implicature, EFL learning / teaching, Illocutionary competence, Implementation of pragmatic instruction.